2018
DOI: 10.24200/sci.2018.51214.2065
|View full text |Cite
|
Sign up to set email alerts
|

Modelling, Control and Simulation of a SCARA PRR-Type Robot Manipulator

Abstract: In this study, a SCARA Prismatic-Revolute-Revolute-type (PRR) robot manipulator is designed and implemented. Firstly, the SCARA robot is designed in accordance with the mechanical calculations. Then, forward and inverse kinematic equations of the robot are derived by using D-H parameters and analytical methods. The software is developed according to the obtained Cartesian velocities from joint velocities and joint velocities from Cartesian velocities. The trajectory planning is designed using the calculated ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The research concluded that BIM + VR jointly assisted planning and design became a direction and the promotion and optimization of VR to BIM would certainly promote its application and development in the field of design teaching and research [8]. Soya-slan et al reflected on the limitations of VR technology in architectural design teaching by analyzing the current situation in the domestic architectural design field [9]. There are many limitations in today's VR technology, such as high hardware cost and inability to be well compatible with architectural design software platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research concluded that BIM + VR jointly assisted planning and design became a direction and the promotion and optimization of VR to BIM would certainly promote its application and development in the field of design teaching and research [8]. Soya-slan et al reflected on the limitations of VR technology in architectural design teaching by analyzing the current situation in the domestic architectural design field [9]. There are many limitations in today's VR technology, such as high hardware cost and inability to be well compatible with architectural design software platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[15] As each joint has a coordinate frame, a transformation matrix can be computed for each link. Therefore, the transformation from the base frame to the end effector can be shown as: Eq.1 [16] The method used to compute the forward kinematics of each of the three robots is the Denavit-Hartenberg (D-H) convention. [17] The notation allows the robots to be converted to a set of transformation matrices, which lets positions of the joints be easily translated to cartesian coordinates by establishing a set of rules on assigning frames.…”
Section: B Forward Kinematicsmentioning
confidence: 99%
“…Facilities of the agro-exporting company Camposol were replicated using equipment such as crates, protective enclosures, smooth and roller conveyors provided by CoppeliaSim, along with those designed in SolidWorks, including the SCARA T6 and UR10 robots and the avocado [48], [49] The designs generated in SolidWorks were then saved in URDF format, including their respective reference systems following the Denavit-Hartenberg method, to enable their visualization in the CoppeliaSim simulation environment to create a highly realistic virtual environment [50][51][52].…”
Section: Pick and Place And Palletizing Cell Simulationmentioning
confidence: 99%